2013
DOI: 10.1186/1472-6882-13-193
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory role of Emblica officinalis in arsenic induced oxidative damage and apoptosis in thymocytes of mice

Abstract: BackgroundArsenic is widely distributed in the environment and has been found to be associated with the various health related problems including skin lesions, cancer, cardiovascular and immunological disorders. The fruit extract of Emblica officinalis (amla) has been shown to have anti-oxidative and immunomodulatory properties. In view of increasing health risk of arsenic, the present study has been carried out to investigate the protective effect of amla against arsenic induced oxidative stress and apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 62 publications
3
59
0
Order By: Relevance
“…Numerous studies have shown that EGCG possesses extensive pharmacological actions in various diseases, including immunosuppression in mice [18]. It has been reported that there is a positive correlation between the application of EGCG and reduction of heavy metal poisoning-related risk in both epidemiological and experimental studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that EGCG possesses extensive pharmacological actions in various diseases, including immunosuppression in mice [18]. It has been reported that there is a positive correlation between the application of EGCG and reduction of heavy metal poisoning-related risk in both epidemiological and experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Blood/tissues were collected as previously described [18]. At the end of the experimental period (30 days), a set of animals were sacrificed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from macrophages, iAs also impairs the development, activation, proliferation and function of lymphocytes (Banerjee et al, 2009;Martin-Chouly et al, 2011;Ostrosky-Wegman et al, 1991). Arsenic exposure affects human lymphocytes following a variety of mechanisms such as increasing free radicals within the cells, oxidative damage, apoptosis, DNA strand damage, modification of DNA bases, crosslinking proteins, lipid peroxidation (Singh et al, 2013). It is evident that Page 17 of 86 A c c e p t e d M a n u s c r i p t arsenic promotes inflammation in vivo and prolonged exposure to arsenic may increase the expression of inflammatory molecules in the body .…”
Section: Effects Of Arsenic On Cardiovascular Systemmentioning
confidence: 99%
“…The animals were exposed to sodium arsenite (Sigma ALDRICH, USA) through drinking water for 30 days (Singh et al, 2013 and. The three doses of arsenic that were selected for the study were 0.01, 0.05 and 0.1 mg/L.…”
Section: Dose Selection For the Studymentioning
confidence: 99%